Differential outcome of neurological HCMV infection in two hematopoietic stem cell transplant recipients - Colombo, Anna Amelia (BioMed Central, 2012)
BACKGROUND: Human cytomegalovirus (HCMV) infection of the central nervous system (CNS) is a rare but life threatening condition which may follow hematopoietic stem cell transplantation. Diagnosis, monitoring and treatment approaches rely on anecdotal reports. CASE PRESENTATIONS: The different outcomes of HCMV CNS disease in an adult and a pediatric T-cell depleted hematopoietic stem cell transplant (HSCT) recipient are reported. In the first case, HCMV encephalitis emerged in the context of simultaneous impairment of the T- and B-cell immunity. Antiviral treatment only reduced viral load in peripheral blood and the patient died. In the second case, an HCMV radiculopathy was observed and antiviral treatment was adjusted on the basis of intrathecal drug level. In addition, donor HCMV-specific cytotoxic T lymphocytes (CTLs) were infused. Viral load in the CNS decreased and the patient recovered from the acute event. In neither case were drug-resistant HCMV variants observed in blood or CNS samples. CONCLUSIONS: T-cell depleted HSCT appears a predisposing condition for CNS HCMV infection since never observed in other HSCT recipients at our center in the last 15 years. Intensive diagnostic approaches and timely aggressive combination treatments might improve clinical outcome in these patients.